Statins benefit in androgen levels and target organ damage in hypertensive males with erectile dysfunction. (3rd October 2022) - Angelis, A; Aggeli, K; Dimitroglou, I; Aznaouridis, K; Ioakeimidis, N; Georgakopoulos, C; Zisimos, K; Koukos, M; Verveniotis, A; Synodinos, A; Lekoudi, E; Alexopoulou, K; et al.
Abstract: Background: Statins may benefit cardiovascular physiology by cholesterol independent or pleiotropic actions. Target organ damage (TOD) amplifies cardiovascular risk in essential hypertension and endogenous testosterone (TT) exhibit vasoprotective effects. Erectile dysfunction (ED) is frequent in hypertensive middle aged men when androgen levels typically fall, impairing thus quality of life. Purpose: To investigate the effect of statins in TT and TOD in hypertensive middle aged men with ED, independently of cholesterol levels. Methods: 248 hypertensive ED males (mean age: 57 yo) with no history of diabetes mellitus or overt cardiovascular disease enrolled the study. Of those 95 (38%) were on statin therapy for treatment of dyslipidemia. There were all screened for the presence of microalbuminuria, defined as urinary albumin loss 30–300 mg in a 24 h urine volume collection. TT, total cholesterol (Tchol) and low density lipoprotein (LDL) levels were measured on blood samples taken before 09:00 am. All individuals underwent a non invasive evaluation of the carotid-femoral pulse wave velocity (PWV), estimation of central pressures and augmentation index (AIx) a parameter of wave reflection amplification (Sphygmocor device). ED severity was assessed by the SHIM-5 score (range: 0–25) and higher values indicate a better erectile ability. Results: In bivariate analysis statin use was positively related to TT (p<0.05 – Figure 1) and negatively to microalbuminuria, Tchol and LDL (p<0.005). Moreover TT was negatively related to PWV, AIx, microalbuminuria (all p<0.005) and positively to the SHIM-5 score (p: 0.003). By linear regression analysis association of TT to statins remained significant after correction for age, BMI, PWV, AIx, Tchol and LDL levels. Conclusions: Statin therapy benefits endogenous testosterone in hypertensive middle aged men with ED and so lessens TOD and enhances erectile ability independently of cholesterol levels. In such population group pleiotropic effects of statins may help restoring androgen levels, decrease cardiovascular risk and ameliorate quality of life. Funding Acknowledgement: Type of funding sources: None.